AN OBSERVATIONAL STUDY TO ASSESS THE ADVERSE DRUG REACTION OF ANTI-ASTHMATIC DRUGS AMONG ADULTS IN WESTERN RAJASTHAN - SWAMI, NARENDRA KUMAR; KUMAR, JIGNESH; BHUJADE, RASHMI; BAGHEL, ANIL SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Asthma is one of the most common chronic illness worldwide. For prevention of exacerbations, patients of bronchial asthma are kept on long-term treatment that is why they are amenable for adverse drug reactions (ADRs). The study was planned to monitor ADRs with intervention of anti-asthmatic drugs in adults visited in medicine outpatient or admitted in inpatient department of a tertiary care teaching hospital. Methods: A cross-sectional study was conducted among 340 asthma patients in collaboration with Department of Medicine for duration of 12 months. Information of patients was collected with the help of semi-structured case record form ADRs along with interventions given that were also recorded. Results: Data analysis was done with the help of SPSS version20.0. Fisher exact test was applied. A total of 340 patients were enrolled in the study. The highest numbers of ADRs were observed with Salbutamol (34.78%). The highest ADRs were noted with Beta2 agonists class of drugs. The main ADRs noted were headache followed by tremors and oral thrush. Statistically significant association was found between presence of ADRs and severity of asthma. Conclusion: Identifying any possible connection between a presenting complaint and drug used is crucial to reduce the risk of ADRs in the future. Appropriate monitoring of ADRs is a key for this. Reduction in ADRs will improve the compliance of patient and ultimately their clinical outcome.